THE SYSTEM OF PERSONNEL STIMULATION - Kasim S. Biktyakov (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
Effective stimulation of employees could attract, motivate and retain the most valuable workers and in this way strengthen the company. The more balanced the company aims and personnel needs are, the more profitable the system of employees’ stimulation will be. Stimulation is a material form, through which the company expresses its gratitude to the employee and assesses his/her work. The author shows that the effective system of stimulation can enhance the results of employees’ work and become a strong incentive to attain the company targets.